Deletion in the gene BruAb2_0168 of Brucella abortus strains: diagnostic challenges. (10th February 2014) - Dean, A. S.; Schelling, E.; Bonfoh, B.; Kulo, A. E.; Boukaya, G. A.; Pilo, P.; Raoult, D.
Abstract Three Brucella abortus strains were isolated from joint hygromas from cows in northern Togo. Two deletions in the 5′ side of the gene BruAb2_0168 were identified. As this gene is used for species identification, these deletions have consequences for diagnostic procedures. Multiple locus variable number of tandem repeat (VNTR) analysis was therefore performed for species identification. The strains showed unique VNTR profiles, providing some of the first genotypic data from West Africa. More molecular and epidemiological data are needed from the region, in order to better understand transmission patterns and develop suitable diagnostic assays.